Credit Extension to MFls: A Comparative Study of Financi Institutions with Special Reference to Micro Financing - Kaur, Harmeet; Tanghi, Bhawdeep Singh (Gyan Management Journal, 2016)
Credit is a major factor in boosting economic development if it is effectively utilized. The govern me:: initiatives to streamline credit operations and delivery systemthrough micro-finance movement strengthening and expansionof credit institutions (SHG's) can definitely help in the revival of r. economy and empowerment of the rural poor. Micro-credit intervention programme has been recognized world over as aneffective tool for poverty alleviation, improving socio-economiccondi of rural poor and their sustainable development. In India too, micro-credit is making a stronghead in its efforts to reduce poverty and empower the ruralpoor. This paper outlines the growth of m credit finance to MF/s by different financial institutions. Also comparison of the growth has demarcated in the study.
Keywords: Micro Finance; Loans disbursed; Loans outstanding; Financial Institutions